Relationships between injury and success in elite Taekwondo athletes - Kazemi, M. (Journal of Sports Sciences, 2012)
The purpose of this study was to determine the rate and type of injury in elite Canadian Taekwondo athletes, before and during competition and to investigate the relationship between past injuries, injuries during competition and success. This retrospective case-series study incorporated Taekwondo injuries sustained by 75 male and female elite Canadian Taekwondo athletes over 10 years and its relationship to athletes' success by means of gaining medals during competition. A logistic regression model (using the Generalised Estimating Equations (GEE) method) was used to investigate the relationship between injuries and success. Injury rate was associated with performance after holding variables constant (Odds Ratio (OR) = 0.124, P = 0.039). Moreover, with each additional injury per match, competitors were 88% (1-0.124) less likely to win a medal. Although not statistically significant, additional injuries prior to competition were associated with a 30% increase in medal prevalence (OR = 1.299, P = 0.203). When comparing athletes (gender, tournament difficulty, injury variables), a competitor who is one year older is 10% less likely to medal (OR = 0.897, P = 0.068). When an additional injury occurred during competition, the athlete was 88% less likely to win a medal. Prevention, correct diagnosis, and immediate therapeutic intervention by qualified health care providers are important.